(untitled) (Cambridge, UK, 2000)
Infanticide by males is relatively common in primates, carnivores, and rodents, although it tends to be rare even in species in which it occurs. Is this behavior pathological or accidental, or does it reflect a conditional reproductive strategy for males in certain circumstances? In this book, case studies and reviews confirm the adaptive nature of infanticide by males in primates, and help to predict which species should be vulnerable to this phenomenon. Much of the book is devoted to exploring the evolutionary consequences of the threat of infanticide by males for social and reproductive behavior and physiology. Written for graduate students and researchers in animal behavior, behavioral ecology, biological anthropology, and social psychology, this book shows that social systems are shaped by ecological pressures, as well as social pressures such as infanticide risk.
Keywords: Primates,Infanticide in animals.,Linh trưởng,Hành vi giết con của động vật; Behavior,Hành vi